A supercritical oil extract of Schisandra chinensis seeds ameliorates Huntington’s disease-like symptoms and neuropathology: the potential role of anti-oxidant and anti-inflammatory effects - Jo, Hyo-Sung; Lee, Youn-Woo; Son, So-Ri; Jang, Dae Sik; Woo Kwon, Tae; Ha, Yujeong; Moon, Sang-Kwan; Kim, Min Soo; Cho, Ik-Hyun (Frontiers in Pharmacology, 2024)
BackgroundHuntington disease (HD), a neurodegenerative autosomal dominant disorder, is characterized by involuntary choreatic movements with cognitive and behavioral disturbances. Up to now, no therapeutic strategies are available to completely ameliorate the progression of HD. Schisandra chinensis has various pharmacologic effects such as antioxidant and anti-inflammatory activities. However, the neuroprotective value of seed oil of S. chinensis (SOSC) has not been elucidated yet. The purpose of this study was to determine neuroprotective effects of SOSC by supercritical fluid extraction against 3-nitropropionic acid (3-NPA)-induced HD-like symptoms and neuropathology in an experimental mouse model.MethodsSOSC (75, 150, and 300 mg/kg/day) was orally pre-administration once daily at 1 hour before 3-NPA intoxication.ResultsSOSC ameliorated movement dysfunction and lethality following 3-NPA intoxication in connection with reduction of lesion area, neurodegeneration/apoptosis, microglial migration/activation, and mRNA expression of pro-inflammatory cytokines/enzymes in the striatum. SOSC inhibited the activation of nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPKs) pathways but stimulated nuclear factor erythroid 2-related factor 2 (Nrf2) in the striatum after 3-NPA intoxication. Schizandrin, a main component of SOSC, reduced protein expression levels of Iba-1 and p-NF-κB in 3-NPA-induced BV2 cells (murine microglia cell line). BV2 cell’s conditioned medium inhibited cleaved caspase-3 in 3-NPA-induced SH-SY5Y cells (a neuroblastoma cell line).ConclusionSOSC might ameliorate movement dysfunction by inhibiting neuropathology through its anti-inflammatory and antioxidant activities in the striata of 3-NPA-intoxicated mice. These findings suggest that SOSC could serve as a promising therapeutic candidate for HD-like symptoms, providing a foundation for future treatment strategies targeting neuroinflammation and oxidative stress.